Meningkatkan Kompetensi Guru Menyusun dan Menerapkan RPP Kurikulum 2013 dalam Pelaksanaan Pembelajaran Melalui Supervisi Akademik Teknik Tagihan di Sekolah Dasar - Suwarti Suwarti (Universitas Sebelas Maret, 2020)
The objective to be achieved in this study is the school action research aims toimprove teacher competence in preparing and implementing the 2013 Curriculum RPP into learning through Academic Supervision of Engineering Bills in Sidomulyo State Elementary School 03. The research subjects in this study are grade I teachers up to grade VI elementary school Negeri Sidomulyo 03 UPTD Pendidikan Ungaran Timur District, Semarang Regency are 6 (six) class teachers, namely: 6 class 1 to 6 class teachers. Techniques and data collection tools through interviews, observation, and documentation methods.Results The results of the Cycle I and Cycle II actions showed a good increase in teacher competence in the preparation and implementation of the 2013 Curriculum RPP in the KBM. While the average for preparing and implementing the 2013 Curriculum RPP in the implementation of learning has increased by 30.77. It was concluded that academic supervision with billing techniques can improve teacher competency in developing and implementing the 2013 Curriculum RPP in implementing learning in Sidomulyo 03 Public Elementary School,Ungaran Timur District, Semarang Regency in 2017/2018 Academic Year.